Pencegahan Depresi Di Kalangan Dewasa Muda Akibat Pandemi Covid-19 Melalui Kampanye Sosial Pada Instagram - Annisa Amalia; Niken Savitri Anggraeni (Universitas Persada Indonesia YAI, 2022)
The Covid-19 pandemic has caused various symptons of depression of thecommunity from mild to severe levels. This is due to the fear of contracting thevirus, the high death rate in Indonesia, economic problems, to confusinginformation on social media, one is young adults. One of the sufferers ofdepression is young adults. To prevent depression, a social campaign throughdigital media is needed to make it easily accessible to this young adults on ofwhich is Instagram. Content with messages and illustrations is expected to be ableto help young adults in preventing depression. This study aims to determine thedesign concept and design execution that appeals to young adults. The methodused is qualitative method with a psychological and design approach to be able toformulate an interesting content through Instagram.